Endothelial NLRP3 inflammasome activation and arterial neointima formation associated with acid sphingomyelinase during hypercholesterolemia - Saisudha Koka; Min Xia; Yang Chen; Owais M. Bhat; Xinxu Yuan; Krishna M. Boini; Pin-Lan Li (Redox Biology, 2017)
The NLRP3 inflammasome has been reported to be activated by atherogenic factors, whereby endothelial injury and consequent atherosclerotic lesions are triggered in the arterial wall. However, the mechanisms activating and regulating NLRP3 inflammasomes remain poorly understood. The present study tested whether acid sphingomyelinase (ASM) and ceramide associated membrane raft (MR) signaling platforms contribute to the activation of NLRP3 inflammasomes and atherosclerotic lesions during hypercholesterolemia. We found that 7-ketocholesterol (7-Keto) or cholesterol crystal (ChC) markedly increased the formation and activation of NLRP3 inflammasomes in mouse carotid arterial endothelial cells (CAECs), as shown by increased colocalization of NLRP3 with ASC or caspase-1, enhanced caspase-1 activity and elevated IL-1β levels, which were markedly attenuated by mouse Asm siRNA, ASM inhibitor- amitriptyline, and deletion of mouse Asm gene. In CAECs with NLRP3 inflammasome formation, membrane raft (MR) clustering with NADPH oxidase subunits was found remarkably increased as shown by CTXB (MR marker) and gp91phox aggregation indicating the formation of MR redox signaling platforms. This MR clustering was blocked by MR disruptor (MCD), ROS scavenger (Tempol) and TXNIP inhibitor (verapamil), accompanied by attenuation of 7-Keto or ChC-induced increase in caspase-1 activity. In animal experiments, Western diet fed mice with partially ligated left carotid artery (PLCA) were found to have significantly increased neointimal formation, which was associated with increased NLRP3 inflammasome formation and IL-1β production in the intima of Asm+/+ mice but not in Asm-/- mice. These results suggest that Asm gene and ceramide associated MR clustering are essential to endothelial inflammasome activation and dysfunction in the carotid arteries, ultimately determining the extent of atherosclerotic lesions.